2020
DOI: 10.3390/microorganisms8111763
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS and 16S RNA Identification of Culturable Gastric Microbiota: Variability Associated with the Presence of Helicobacter pylori

Abstract: Helicobacter pylori is the main bacteria associated with gastroduodenal diseases. Recent studies have reported that gastric microbiota might be modified by the H. pylori colonization, favoring gastric lesions′ development. In Chile, the region of La Araucanía concentrates a high risk of gastric cancer associated with Helicobacter pylori colonization, rurality, poverty, and Mapuche ethnicity. Hence, we aimed to identify the culturable gastric microbiota and characterize its variability at different stages of ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Another diagnostic challenge is the correct identification on a species level. In some laboratories, matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) may not be as readily available as in others, even though this method has been considered the gold standard since its introduction into microbiological diagnostics more than a decade ago [ 48 , 49 , 50 ]. As described above, significant interspecies differences in clinical relevance, pathogenicity, and even antimicrobial susceptibility exist [ 50 , 51 ].…”
Section: The Diagnostic Complexities—how To Distinguish Between Infection and Contaminationmentioning
confidence: 99%
“…Another diagnostic challenge is the correct identification on a species level. In some laboratories, matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) may not be as readily available as in others, even though this method has been considered the gold standard since its introduction into microbiological diagnostics more than a decade ago [ 48 , 49 , 50 ]. As described above, significant interspecies differences in clinical relevance, pathogenicity, and even antimicrobial susceptibility exist [ 50 , 51 ].…”
Section: The Diagnostic Complexities—how To Distinguish Between Infection and Contaminationmentioning
confidence: 99%
“…It has been suggested that the presence of specific species such as Streptococcus mutans and Prevotella intermedia in the bio-film could inhibit the growth of H. pylori strains. [34]- [36] It also has been shown that Porphyromonas spp and Fusobacterium nucleatum can adhere to and trap H. pylori. [35] In addition to its effect on health, the incidence of Wolinella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting technique utilizing MALDI-TOF MS demonstrated a microbiota modification owing to H. pylori colonization linked to the gastric epithelial condition, implying a potential function for the microbiota in the development and progression of gastric disorders [ 82 ]. The presence of Neisseriaceae , Streptococcaceae , Enterobacteriaceae , and Lactobacillaceae families after H. pylori infection was seen, although Gram-positive bacteria such as Gamellaceae , Propionibacteriaceae , Granilucatella , Bacillaceae , and Corynebacterium species were removed.…”
Section: Matrix-assisted Laser Desorption/ionization–time-of-flight—m...mentioning
confidence: 99%